Proven and reliable methods of early speech therapy intervention for children with autism spectrum disorder - Kharatyan, Kristina; Hovyan, Gohar
The purpose of our research is to identify the effective tools for early Speech therapy intervention in working with children with Autism Spectrum Disorder (ASD) in order to provide their speech forming and development by using confinable methods. Besides, the purpose includes the thesis about high effectivity of systematic complex approach in case of work with ASD. Current research is based on theoretical materials from professional literature and on 14 years of own personal speech therapy professional experience. It is concluded that methods used in the speech therapy work with ASD children are effective in application, but as a result of the individual approach of the child's speech and communication, their combination at the appropriate stage of development provides a higher result. We emphasize the development of established methods and means of early speech intervention in the work with ASD, the development of a systemic approach and the introduction of conditions that will facilitate their early speech therapy intervention.
Keywords: Autism syndrome